Ruin and rising. #3 - Bardugo, Leigh (Henry Holt and Company New York, 2014)
The Darkling rules Ravka from his shadow throne. Now the nation's fate rests with a broken Sun Summoner, a disgraced tracker, and the shattered remnants of a once-great magical army